EXTROVERT VS INTROVERT: INVESTIGATING STUDENTS’ CHARACTERISTICS IN RELATION TO STUDENTS’ ENGLISH PROFICIENCY - Salma Mu'min Shiddiq; Lulud Oktaviani (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2022)
The objective of the present study was to investigate whether there was a correlation between students’ characteristics and students’ English proficiency. The sample was made up of 44 English Education students in a private university in Bandarlampung.A set of online questionnaire with a total of 30 questions was distributed in order to collect information about students’ characteristics as well as their English proficiency score.Results suggest that there was a significant difference between extroverted and introverted students in relation to their English proficiency. The findings indicate that the significance value of the p-value is 0.005 (<0.05). Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. The magnitude of the correlation is -0.440 which indicates that the correlation is a moderate negative (downhill) linear relationship. As the EPT score increases, the students tend to be more introverted.